The Convention of The Hague and the Constitutional Debates in the Estates of Flanders and Brabant, 1790-1794 - Van Gelder, Klaas (Early Modern Low Countries, 2017)
Following the Brabant Revolution and the declaration of independence of the Southern Netherlands, Vienna made a series of constitutional assurances to the rebels while at the same time preparing to recover the region by force. In December 1790, these promises culminated in the Convention of The Hague, in which Emperor Leopold II – under allied pressure – pledged to restore the ancient constitutions of the Southern Netherlands, which led to constitutional debates among the rebellious provinces. This article examines why the imperial commitments did not placate the estates of the leading provinces, Flanders and Brabant. The Flemish Estates grasped the opportunity to draft their own constitutional charter; Brabant primarily pursued additional safeguards to protect its charter, the Joyous Entry. I argue that these debates chiefly reflect the language of ancient constitutionalism and in essence served conservative goals even as actual circumstances compelled the estates to integrate innovative concepts in their reasoning. Moreover, these debates are very telling for the constitutional sensitivities in the separate Southern Netherlandish regions. Embedded as they were in specific regional constitutional traditions, these debates produced different outcomes in Flanders and Brabant.